Development Of A Systematic, Accountable And Inclusive Mechanism Through Talent Management In Preparing Future Leaders - Bustanul Arifin Caya; Masydzulhak Djamil; Ahmad Hidayat Sutawijaya; Dinar Nur Affini (Universitas Mercu Buana, 2022)
The Bureaucratic performance is generally characterized by the low quality of public services. Talent management is a mechanism in order to attract, motivate and retain qualified leaders. Therefore, this study aims to analyze the development of talent management in order to prepare future leaders. Talent management is the result of a paradigm shift in human resource management. Experts divide the definition of talent management into two spectrums, namely exclusive and inclusive. Both definitions aim to increase the organization's opportunities in order to increase the achievement of its objectives. The success of implementing talent management in various countries and the private sector has encouraged the Indonesian government to adopt talent management as part of the bureaucratic reform agenda. This study showed that the implementation of talent management requireed 3 values including: 1) A transparent process is one of the keys to the successful implementation of talent management in public institutions; 2) Several methods that can be used are assessment center, 9 talent boxes and development program; and 3) the talent management implementation process requires commitment from all elements of the institution. In addition, the development of talent management is formed in several stages. 1) Establishment of regulations to support the development of talent management; 2) Establishment of an Assessment Center as a center for assessing the competence of prospective leaders; 3) Reorientation of the preparation of position competencies through the Assessment Center; 4) Talent management development; 5) Integration of talent management programs with education and training through the utilization of the talent pool; 6) Establishment of a Corporate University as part of the commitment to the talent development program in the talent pool.